A Prospective Observational Study of Hypomagnesemia in Critically Ill Paediatric Patients - Chandrashekhar, Channanayaka; Pillai, Reshmi; Vasudev, Prajwala Hassan; Babu, Tirin; Panachiyil, George Mathew (Journal of Nepal Paediatric Society, 2020)
Introduction: Magnesium deficiency, a common finding in critically ill patients, is associated with increased need for respiratory support, increased duration of ICU stay and mortality. The primary objective of our study is to assess the prevalence of hypomagnesaemia in critically ill children (requiring inotropic support, respiratory support, and fluid resuscitation) on admission in the Paediatric Intensive Care Unit (PICU). The secondary objective is to evaluate its relationship with the length of hospital stay and mortality. Methods: This prospective observational study was conducted in the PICU of a tertiary care hospital. In this study, serum magnesium levels at admission were measured along with other laboratory tests, after informed consent. Serum magnesium levels were assayed in our laboratory. The normal range of serum magnesium in our lab is 1.7-2.7 mg/dl. During admission in PICU, there was follow-up for ionotrope administration, need for mechanical ventilation, APACHE II score, PICU length of stay and mortality. Results: In this study, 350 critically ill children requiring hemodynamic / respiratory support were chosen. However, 83 children were excluded from study as they were discharged against medical advice. The prevalence of hypomagnesemia in this study was 43.4%. There was no significant association between hypomagnesemia, duration of hospital stay and mortality. Conclusion: Hypomagnesaemia is a common finding in critically ill paediatric patients, however there is no significant association noted in regards to length of hospital stay, duration of mechanical ventilation, inotropic support and mortality.